Connected slots antenna array feeding a high-gain lens for wide-angle beam-steering applications. Issue 1 (19th February 2022) - Aziz, Imran; Öjefors, Erik; Dancila, Dragos
Abstract: This paper presents a 60 GHz connected slots linear-phased array feeding a high-gain semi-symmetric lens antenna. This design provides high gain, broadband, and beam-steering capabilities for gigabit rate access and backhaul communications. The connected slots antenna array (CSAA) is excited at 16× equidistant points which not only yields spatial power combining but also allows the progressive phase changes to steer the beam in ±45 ° in azimuth plane. To characterize the CSAA-fed lens antenna, four different power splitters are fabricated which steer the main beam in 0, 15, 30, and 45 ° . The lens is designed in a way to overcome the scan loss and get comparatively higher gain when beam is steered away from the broadside. The measured results show 25.4 dBi maximum gain with 3 dB gain bandwidth covering the full band 57–66 GHz whereas 3 dB beam-steering range is ±45 ° for all frequencies. Besides, the half power beamwidth is 6 and 10 ° in elevation ( E -plane) and azimuth plane ( H -plane), respectively.